ISOLASI BAKTERI POTENSIAL PENDEGRADASI DIBENZOTIOFENA DARI TANAH TERCEMAR MINYAK BUMI DI BULUH TELANG LANGKAT SUMATERA UTARA - Hendra Prasetya, I Putu; Wayan Gunam, Ida Bagus; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 1 (2016): Maret)
This research aimed to isolate some of potential bacteria which could degrade dibenzothiophene (DBT). The bacteria were isolated from the soil which has been contaminated by petroleum for many years in Buluh Telang Langkat North Sumatera. This experiment was also conducted to find out the isolate that had the highest degradation rate of DBT. The results showed that the isolated bacteria had a different ability to degrade dibenzothiophene with OD660 ranged from 1.100 to 1.137 and the degradation rate ranged from 42.62% to 69.88%. The isolate of LSU20 had the highest ability to degrade DBT. The isolated bacteria which was incubated for 96 hours at 45 o C in shaking condition at 150 rpm could degrade 69.88% of 200 ppm DBT in tetradecane. Keywords: Isolation, biodesulfurization, dibenzothiophene
Keywords: 86,